PD-1 Interaction with PD-L1 but not PD-L2 on B-cells Mediates Protective Effects of Estrogen against EAE - Bodhankar, Sheetal (2013)
Increased remissions in multiple sclerosis (MS) during late pregnancy may result from high levels of sex steroids such as estrogen and estriol. Estrogen (E2=17β-estradiol) protects against experimental autoimmune encephalomyelitis (EAE), but the cellular basis for E2-induced protection remains unclear. Treatment with relatively low doses of E2 can protect against clinical and histological signs of MOG-(35-55) induced EAE through mechanisms involving the PD-1 coinhibitory pathway and B-cells. The current study evaluated the contribution of PD-1 ligands, PD-L1 and PD-L2, on B-cells in E2-mediated protection against EAE in WT, PD-L1(−/−) and PD-L2(−/−) mice. Unlike PD-L2(−/−) mice that were fully protected against EAE after E2 treatment, E2-implanted PD-L1(−/−) mice were fully susceptible to EAE, with increased numbers of proliferating Th1/Th17 cells in the periphery and severe cellular infiltration and demyelination in the CNS. Moreover, transfer of B-cells from MOG-immunized PD-L1(−/−) or PD-L2(−/−) donors into E2-preconditioned B-cell deficient μMT(−/−) recipient mice revealed significantly reduced E2-mediated protection against EAE in recipients of PD-L1(−/−) B-cells, but near-complete protection in recipients of PD-L2(−/−) B-cells. We conclude that PD-1 interaction with PD-L1 but not PD-L2 on B-cells is crucial for E2-mediated protection in EAE and that strategies that enhance PD-1/PD-L1 interactions might potentiate E2 treatment effects in MS.